Analysis of the Influence of BOPO, NIM and Inflation on the Profitability of Bank BRI Syariah in 2013-2020 - Alam, Azhar; Setyowati, Eni; Wiguna, Aditama Chandra; Nizam, Renaldi Sahrul (Talaa : Journal of Islamic Finance, 2022)
This study analyzes factors affecting BRI Syariah Bank's profitability in Indonesia. This study sampled BRI Syariah Bank's 2013-2020 yearly financial statements that fit the study's requirements. Data for Bopo, Nim, Inflation, and Roa come from the official BRI Syariah bank and Bank Indonesia (BI) websites for 2013 – 2020. This study uses the ROA ratio as a metric of BRI Syariah Bank's profitability and BOPO, NIM, and Inflation as independent variables. This study uses the Ordinary Least Square (OLS) data analysis method to obtain a thorough picture of the relationship between variables using Eviews10 software. According to study, BOPO negatively affects ROA (Return on Assets). Operating Costs and Operating Income (BOPO) are less significant than required. The study shows that BOPO has a detrimental impact on ROA (Return on Assets). NIM and inflation study results had little impact on BRI Syariah Bank's ROA. This study reveals that Islamic banks are resilient to inflation and don't rely on profit margins. This study suggests Islamic banks reduce operating costs to boost profitability.